Perancangan User Experience Aplikasi Pembelajaran Iqro menggunakan Pendekatan Gamifikasi - Mujiburrahman Haekal Fajry; Lutfi Fanani; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Iqro is one method of learning the alquran that makes it easy to learn to read and recite the alquran. There are many iqro learning applications on google playstore that can be used as learning media. However, most of these applications only copy-paste iqro pages into the applications, resulting in applications that cannot be read and the color selection and layout that seems monotonous and unattractive loses the motivation for self-study. Therefore, this study intends to design a user experience or user experience for an iqro learning application using a gamification approach and player centered design method in the hope of producing designs and prototypes that are in accordance with what is needed by potential users. This research is implementative-design with the aim of producing a product as a solution to the problems raised in the study. In this study testing was carried out using the User Experience Questionnaire, the results were obtained in the form of 3 of the 6 test scales getting good results, then the rest got results above the average. Then in this study a playtest was also carried out on 5 children, resulting in data showing that almost all children are happy to learn while playing, on the grounds that it is more fun to do the missions given by the system. The results obtained about 4 system improvements that were immediately implemented. Testing is carried out only with 1 iteration because the test is deemed to have obtained results in accordance with the expectations and expectations of the examiner.